PREDIABETES AND RISKS FOR ALL-CAUSE AND CARDIOVASCULAR MORTALITY BY HYPERTENSION STATUS: RESULTS FROM THE NATIONAL HEALTH AND NUTRITION EXAMINATION SURVEYS. (April 2021) - Liu, Lin; Huang, Yuqing; Huang, Jiayi; Chen, Chaolei; Yu, Yuling; Shen, Geng; Lo, Kenneth; Feng, Yingqing
Abstract : Objective: Current recommendation suggests prediabetes testing for adults with overweight or obesity who have at least one cardiovascular risk factor. Given the detrimental effects of combined prediabetes and hypertension on CVD events, it is important to understand whether testing should be conducted for adults with hypertension regardless of other cardiovascular risk factors Design and method: Participants from the 1999–2014 National Health and Nutrition Examination Surveys (NHANES) aged over 18 years without diabetes were enrolled for analysis. Participants were classified according to their status of prediabetes and hypertension, and followed up for cardiovascular and all-cause mortality till 31 December 2015. Cox proportional hazards models were built to estimate the hazard ratios (HR) for all-cause and cardiovascular mortality among participants with prediabetes, hypertension, and both. Results were also stratified by age, gender and demographic backgrounds to explore subgroup differences in associations. Results: A total of 34, 047 participants with median follow-up period of 8.4 years were included in analysis. Prediabetes was defined as fasting plasma glucose between 100 and 125 mg/dL, or hemoglobin A1c between 5.7 and 6.4%, or self-reported hypoglycemic drug use. Hypertension was defined as systolic/diastolic blood pressure over 140/90 mmHg and/or self-reported antihypertensive medication use. At baseline, 5011 (14.7%) of them had combined prediabetes and hypertension. When compared with participants without prediabetes nor hypertension, prediabetes alone was not associated with all-cause (HR [95% CI]: 1.12 [0.93, 1.34]) nor with cardiovascular mortality (1.30 [0.74, 2.29]); hypertension alone was significantly associated with all-cause (HR [95% CI)]: 1.30 [1.11, 1.52]) and cardiovascular mortality (1.97 [1.22, 3.16]); combined prediabetes and hypertension was significantly associated with all-cause mortality (HR [95% CI]): 1.40 [1.19, 1.65]) and cardiovascular mortality (2.40 [1.49, 3.85]).According to subgroup analysis, participants with combined prediabetes and hypertension had a higher risk of all-cause mortality among those aged < 60 (HR: 2.19), White population (HR: 1.41) and male participants (HR:1.52). Conclusions: Prediabetes might elevate the risks of all-cause and cardiovascular mortality among people with hypertension. Figure. No caption available.